Analysis of the Effect of Battery Voltage Drop on Light Intensity on LED and Hologen Type Main Lights in Gentayu UNDIP Electric Cars to Get Good Lighting - Setiyawan, Trio; Kristiawan, Timotius Anggit (Politeknik Negeri Semarang, 2023)
Abstrak - The Gentayu UNDIP electric car requires a lighting system, especially the main lighting system, namely the headlights which must have sufficient light but must be economical in power consumption, because the power used uses a battery that is separate from the main battery for propulsion. So that with a separate battery, the available power is limited, for charging the battery a separate mechanism is made and it can be charged simultaneously with charging the main battery for the Gentayu UNDIP electric car. we will try to do a special analysis of the intensity of light in the lighting system of the main lighting system, to get data on the effect of battery power on light intensity. The test was carried out by observing the decrease in light intensity on two types of lamps, namely LED lamps and halogen lamps. 1x10 Lux every 15 minutes with an average voltage drop of 0.06 volts for every 15 minutes. Meanwhile, for halogen type lamps, the average decrease in light intensity is 6x10 Lux every 15 minutes with a voltage drop of 17 volts, so even though the use of LED type lamps has low power consumption in its use, but a decrease in light intensity when used for a long time cannot be avoided, so it is necessary to make a mechanism for the Gentayu UNDIP electric car so that the battery voltage is maintained when the lighting electrical system is used.